Reclaiming Radicalism: Discursive Wars and the Left - Giorgos Charalambous (tripleC: Communication, Capitalism & Critique)
The aim of this article is to identify and discuss a number of labels that have been increasingly used to describe, categorise and study the contemporary radical left – the movements and parties of the socialist tradition and its contemporary derivatives – pointing to the deeply political implications of these trends. More specifically, ‘extremism’, ‘populism’ and ‘nationalism’ as signifiers of what left radicalism looks like are scrutinised in terms of both the political logic and the historical background behind their use, and the challenges they raise for emancipatory, progressive politics. A plea for recasting contemporary social and political struggles for equality and rights is subsequently articulated, the central conviction advanced being terminological: the left’s struggles today must rise above the verbal smoke of the predominant discourse about this political space. It is a key task to appropriately qualify those terms that taint contemporary radicals with colours which do not represent them or fall far short from defining them. Put simply, if the radical left is to succeed electorally and channel its vision into society effectively it needs to reclaim its chief identity trait in the public sphere: left radicalism itself. Reclaiming radicalism entails a number of strategic tasks. These are laid out in terms of imperative discursive articulations, which are, however, paralleled by particular political actions on the ground that can either confirm or undermine any terminological claims.